Influence of processing on the technological and sensory quality of bread: an overview - Lomonaco, Angela; Galgano, Fernanda; Condelli, Nicola; Paganoni, Cristiano; Carmela Mecca, Lucia; Di Cairano, Maria (Italian Journal of Food Science, 2025)
The quality of bread is mainly affected by three key phases of production: mixing, leavening, and baking. Each step contributes to the final rheological and sensory properties of the bread. However, especially during the mixing phase, the choice of ingredients and the processing parameters, such as mixing time, dough temperature, mixing speed, and total water content, affect the development of the dough. The properties and behavior of dough are measured by rheological tests, which are crucial from the perspective of optimization. This paper aims to shed light on both technological and sensory aspects of factors that affect the quality of bread.